Create An E-Raport Application Using The Laravel Framework And Mysql - Tahari, Arzan; Kalsum, Toibah Umi; Fredricka, Jhoanne (Jurnal Media Computer Science, 2025)
Learning outcome reports are written evidence of student learning progress over time. The data recorded in the student learning outcome report can be used to track student progress, identify student strengths and weaknesses in several subjects. This research aims to develop a web-based E-Raport application using the Laravel Framework and MySQL. This research was conducted at SD Negeri 33 Seluma. Located in Lubuk Betung Village, Semidang Alas Maras District, Seluma Regency, Bengkulu Province from October to November 2024. The result of this research is the creation of an E-Raport application that has features of managing student data, inputting grades, calculating grades, and making report cards.